STRATEGI PENGAJARAN BAHASA INGGRIS UNTUK SISWA DENGAN DISABILITAS INTELEKTUAL DI SEKOLAH LUAR BIASA NEGERI BONE BOLANGO - El Walidayni Kau, Magvirah; Danial, Haris; Fatmatul Zanna, Nur (Berajah Journal, 2025)
This study explores the teaching strategies used by English teachers at SLB Negeri Bone Bolango for students with intellectual disabilities. The research aims to identify the types of strategies applied in teaching English to these students. Using a qualitative descriptive method, data were collected through observations and interviews conducted in June 2024. The findings indicate three main strategies implemented by teachers: Direct Method, Total Physical Response (TPR), and Individual Learning. Each strategy is adapted to the students' needs and supported by appropriate media and approaches. Teachers face challenges such as students’ limited vocabulary comprehension, limited time for individualized instruction, and the need for an inclusive learning environment. To address these, teachers employ visual aids, physical activities, and adjust learning materials. The results reveal that the application of suitable teaching strategies can enhance students’ understanding and active participation in learning English.